2019
DOI: 10.1140/epjc/s10052-019-7195-4
|View full text |Cite
|
Sign up to set email alerts
|

The trace of the trace of the energy–momentum tensor-dependent Einstein’s field equations

Abstract: The f (R, T ) gravity field equations depend generically on both the Ricci scalar R and trace of the energy-momentum tensor T . Within the assumption of perfect fluids, the theory carries an arbitrariness regarding the choice of the matter lagrangian density L, not uniquely defined. Such an arbitrariness can be evaded by working with the trace of the theory field equations. From such an equation, one can obtain a form for L, which does not carry the arbitrariness. The obtained form for L shows that the f (R, T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 149 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Harko et al have demonstrated that the covariant derivative of energy-momentum tensor does not vanish in the theory giving the non-geodesic motion of a massive test particle and also it has been noted that an extra force remains effective because of the matter-geometry coupling developed in the theory. Later, Moraes presented that the extra force may vanish for L m = − p in the non-relativistic dust matter case [42]. Under analogous noninteracting two fluid structures as presented by Harko et al, S. Chakraborty has described [43] that the conservation of energy-momentum tensor can be taken into account for some specific forms of the f (R, T ) function.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Harko et al have demonstrated that the covariant derivative of energy-momentum tensor does not vanish in the theory giving the non-geodesic motion of a massive test particle and also it has been noted that an extra force remains effective because of the matter-geometry coupling developed in the theory. Later, Moraes presented that the extra force may vanish for L m = − p in the non-relativistic dust matter case [42]. Under analogous noninteracting two fluid structures as presented by Harko et al, S. Chakraborty has described [43] that the conservation of energy-momentum tensor can be taken into account for some specific forms of the f (R, T ) function.…”
Section: Introductionmentioning
confidence: 95%
“…It is to be noted that because of the extra terms appearing in the field equations, the f (R, T ) theory of gravity can be regarded as a two fluid model [42]. Further, defining T I µν for an anisotropic geometric matter distribution, we can express it as [29] T νI µ = diag −ρ I , P I r , P I t , P I t ,…”
Section: Modified Einstein Field Equations In F (R T ) Gravitymentioning
confidence: 99%
“…Since the choice of the matter Lagrangian L m = −p sq is not unique for a perfect fluid, Moraes [63] has eliminated this arbitrariness by deriving the following matter Lagrangian:…”
Section: The Model and Field Equationsmentioning
confidence: 99%